2019
DOI: 10.15244/pjoes/99107
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation Rates and Heavy Metal Concentrations in the Tidal Flats of North Vietnam

Abstract: Tidal flats, a type of coastal wetland, play an important role by providing space for socioeconomic development, various resources, and high biodiversity. Connected to the mainland, tidal flats are affected by both human activities and natural processes, which cause erosion, accumulation of pollutants, and loss of biological resources. Studying the sediments of tidal flats can provide details of natural phenomena and human activities as key factors to understand sedimentary processes and human impacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Hoai et al [ 70 ] discovered that the concentrations of HMs (Cu, Zn, Pb, As, and Cd) in the sediments of tidal flats in northern Vietnam (Quang Ninh to Ninh Binh) provinces increased over time. Cu, Pb, and As concentrations in sediments from the center to the south surpassed the ISQG standards.…”
Section: Resultsmentioning
confidence: 99%
“…Hoai et al [ 70 ] discovered that the concentrations of HMs (Cu, Zn, Pb, As, and Cd) in the sediments of tidal flats in northern Vietnam (Quang Ninh to Ninh Binh) provinces increased over time. Cu, Pb, and As concentrations in sediments from the center to the south surpassed the ISQG standards.…”
Section: Resultsmentioning
confidence: 99%
“…At the Ba Lat estuary, at some monitoring time, Fe concentrations in the water were from 2.2 to 9.7 times higher than the allowed value QCVN 10-MT: 2015/BTNMT [12] whereas Zn concentrations were from 1.28 to 5.12 times higher than the standard limits [14]. High contents of trace metal elements (Cu, Zn, Pb, As, Cd, and Hg) in the coastal sediment of North Vietnam, including ai Binh and Nam Dinh provinces, were also observed in different studies [15,16]. is may affect the life and quality of the fishery and aquacultural seafood in this area.…”
Section: Introductionmentioning
confidence: 87%
“…both point and dispersal wastes sources. In our case, the pollution in the coastal water and sediment of the ai Binh and Nam Dinh provinces probably comes from inland (domestic, agricultural, and industrial wastewater)[12,15,18]. Nguyen et al[17] studied on trace metal element concentration in surface soil samples collected from different land use types in agricultural land in Nam Dinh Province and found that Cr mainly originated from a natural source.…”
mentioning
confidence: 87%
See 2 more Smart Citations